GAMIFICATION — AS A TOOL IN TEACHING ENGLISH - Tashmukhammedova Gulnoza Zayniddinovna (Web of Journals Publishing, 2024)
This article talks about the methodology of teaching English, the use of modern technologies in learning foreign languages, the role and effect of gamification in language learning.In this article, we will explore the benefits of gamification in English language learning, how to implement gamification in the classroom, the challenges and limitations of gamification, and tips for successful implementation.
Keywords: ELT, gamification, methods, motivation and engagement ,participation, positive and fun environment, education, lesson plan, platforms, education approach, communication.